The applicability of international law to armed conflicts involving non-state armed groups: between status and humanitarian protection - Ioannis, Kalpouzos (2011)
This is a thesis about the applicability of the jus in bello to armed conflicts involving non-state armed groups. The thesis focuses on the thresholds of applicability. These are the definitions of actors and situations that activate the applicability of the jus in bello. The aim is to illuminate and critique the regulatory rationales behind the different definitions of actors and situations in the different thresholds. The evolution of the thresholds is reviewed chronologically. Accordingly, the enquiry ranges from the 19th century doctrines of recognition of belligerency and insurgency, through common article 3 and Additional Protocols I and II, to the law developed by the ICTY and included in the Rome Statute for the International Criminal Court. While the thresholds constitute the centre of the enquiry, their meaning and function are further elucidated by the analysis of the process of their assessment, as well as the extent of the substantive legal regime they activate.